2004
DOI: 10.2320/matertrans.45.1101
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory and Mechanical Properties of Biomedical Ti-Sc-Mo Alloys

Abstract: Ni-free Ti-Sc-Mo shape memory alloys are designed as a substitute for Ti-Ni alloys in the biomedical field. From results of bending and recovery test with heating, Ti-Sc-Mo alloys were found to have superior shape memory effect. The optimum composition for the shape memory effect was Ti-4.0 to 6.0Sc-6.0Mo alloys. The maximum shape recovery strain in the Ti-5.0Sc-6.0Mo alloy was 5.3% measured through cyclic tensile deformation. Vickers hardness and 0.2% proof stress were remarkably decreased and elongation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Figures 2(c) and (d) show optical micrographs of 0.2N alloys cooled at 270 K/s and 2 K/s, respectively. As previously reported, 12) thermally induced martensite is completely suppressed by 0.2 mass% nitrogen addition even at the highest cooling rate of 270 K/s. Precipitation of equilibrium phase from grain boundary is observed only at the slowest rate of 2 K/s.…”
Section: Initial Microstructuresupporting
confidence: 85%
See 1 more Smart Citation
“…Figures 2(c) and (d) show optical micrographs of 0.2N alloys cooled at 270 K/s and 2 K/s, respectively. As previously reported, 12) thermally induced martensite is completely suppressed by 0.2 mass% nitrogen addition even at the highest cooling rate of 270 K/s. Precipitation of equilibrium phase from grain boundary is observed only at the slowest rate of 2 K/s.…”
Section: Initial Microstructuresupporting
confidence: 85%
“…1) Since then, several titanium alloys exhibiting the shape memory effect and/or superelasticity have been reported in Ti-Mo-Al 2) and Ti-V-Al 3) ternary alloys and in a Ti-10V-2Fe-3Al alloy 4) which is one of the practical titanium alloys for structural use. Recently, much attention has been paid to Ni-free titanium shape memory and superelastic alloys for biomedical use due to the cytotoxicity of Ni, leading to the recent development of Ti-Nb based [5][6][7][8][9] and Ti-Mo based [10][11][12] alloys. Previous studies mostly focused on finding out the optimum composition for shape recovery in the quenched state.…”
Section: Introductionmentioning
confidence: 99%
“…1) The superelasticity has been also reported in ternary alloys such as Ti-Nb-Sn, 2) Ti-Nb-Zr, 3) Ti-Nb-Ta, 4) Ti-Nb-Al, 5) Ti-Nb-Pt 6) and Ti-Nb-O. 7) In addition, it has been also reported that the superelasticity was observed in Ti-Mobased alloys such as Ti-Mo-Sn, 8) Ti-Mo-Sc 9) and Ti-MoGa. 10) However, these -Ti base superelastic alloys exhibit the shape recovery strain of only 3% at the maximum.…”
Section: Introductionmentioning
confidence: 87%
“…This has led to the development of Ni-free -Ti base shape memory alloys which consist of only non-toxic elements. [1][2][3][4][5][6][7][8][9][10][11][12] In -Ti alloys, superelasticity is associated with a stress induced martensitic transformation from the phase (bcc) to 00 martensite phase (orthorhombic) by loading and its reverse transformation by unloading. The control of the martensitic transformation temperatures by the adjustment of the amount of -stabilizer elements such as Nb, Mo and Ta is necessary to obtain the superelasticity in Ti-base alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For example the shape memory behavior of -type Ti-base alloys, such as Ti-Mo [3][4][5][6][7], Ti-Nb [8][9][10][11][12] and Ti-Ta [13][14][15][16] alloys, has been reported. The excellent cold-workability of -type Ti-base shape memory alloys have made them attractive for practical applications as new smart materials, since they can be easily fabricated to fine wires and thin plates of dimensions suitable for actual applications.…”
Section: Introductionmentioning
confidence: 99%